Pengaruh Pengalaman Penguasaan PLP, Emosi, Dan Dukungan Emosional Terhadap Motivasi Mahasiswa Menjadi Guru Ekonomi Di Mediasi - Nasukha, Rofan; Harini, Harini; Sabandi, Muhammad (Universitas Hamzanwadi, 2024)
Motivation is considered to be one element in increasing interest in becoming a teacher. Data from the UNS Career Development Center shows that students who graduate from the Faculty of Teaching and Education, Sebelas Maret University who work as teachers tend to have low levels. This research is quantitative research with a survey method. The population in this study were 138 Sebelas Maret University students and Jendral Soedirman University students. The analysis in this research uses path analysis. Based on the test results, it shows that (1) the experience of mastering PLP in MBKM has a positive and significant effect on students' self-efficacy decisions (2) emotions have a positive and significant effect on students' self-efficacy decisions (3) emotional support has a positive and significant effect on efficacy decisions students' self-efficacy (4) self-efficacy decisions have a positive and significant effect on students' motivation to become economics teachers.